Hakikat Dan Tujuan Pendidikan Islam Dalam Persektif Hadits - Elsya Frilia Ananda N; Dinda Putri Hasanah; Lidya Zanti; Naila Hafizah; Wismanto Wismanto (Pusat Riset dan Inovasi Nasional, 2024)
Islamic education can be described as a process that combines knowledge with spiritual strength to preserve individuals to become a fullest human beings against the norms of Islam with this important importance of Islamic values such as faith, worship, and good behavior by emphasizing parent roles in teaching children about God, prayer and moral behavior to form obey and obeyed human beings. The purpose of this study is to discuss the perfect policies and purposes of the Himist and the Qur'an produce individuals committed to Islam with faith, knowledge, work ethics, and noble characters in order to fulfill their role as the servant of the earth and the servant of Allah swt. This research uses a qualitative research method with library approach or library research (data library,) data collection by finding sources and mercryuctions from various sources such as books, journals, articles and existing research. The results of the study show that the purpose of Islamic education is the effort of each individual to defend their identity and help them develop their full potential for the good and perfection of this world and then based on the Qur'an and Hadist and Islamic education can be fundamental components from the education